Pengaruh Sistem Informasi Akuntansi Manajemen dan Sistem Pengukuran Kinerja terhadap Kinerja Manajerial Rumah Sakit di Kota Padang - Pumadari, Indah; Handayani, Dian Fitria (Jurnal Eksplorasi Akuntansi, 2025)
This research aims to examine the influence of management accounting information systems and performance measurement systems on managerial performance in hospitals. This type of research data uses primary data. Primary data was obtained from questionnaires filled out by respondents. The sample used in this research was 136 employees from the planning, procurement, administration, treasurer, PPK, budget, finance and supervision departments of hospitals in Padang City. The statistical data analysis technique used in this research is multiple regression analysis. The results of this research show that the management accounting information system and performance measurement system have a significant positive effect on managerial performance at Padang City Hospital. The implication of this research is that the management accounting information system and performance measurement system will work well if a leader knows and understands the problems that exist in a department in the organization. Therefore, there is a need for leaders who are reliable, expert and have competence in leading a department in the organization in order to create maximum performance.